GAMBARAN TEKANAN DARAH PADA REMAJA OBES DI KABUPATEN MINAHASA - Tooy, Rosie (eBiomedik, 2013)
Abstract: The incidence of obesity continues to rise everywhere. Obesity can increase the risk of high blood pressure. For adolescents, hypertension is also a problem because adolescents with hypertension can continue in adulthood and also with higher chance of morbidity and mortality.  According to the data from Riskesdas for the year 2007, the prevalence of hypertension in adolescents is 9%. The Riskesdas data for the year 2010 also show that prevalence of obesity in adolescents 19,1%. This study aims to describe the blood pressure in obese adolescents at Minahasa district. This study is cross-sectional descriptive approach, with the sample amounted to 54 people. The test results found that 104 students have a waist circumference greater than a normal waist should be. Beside that, the  results showed an outline of blood pressure in obese adolescents at Minahasa district is 29,62% that has hypertension. There are 16 subjects from 54 subjects studied had the blood pressure greater than normal limits while 38 subjects studied had blood pressure within normal limits. Keywords: Blood Pressure, Obesity   Abstrak: Angka kejadian obesitas terus meningkat dimana-mana. Obesitas dapat meningkatkan resiko terjadinya penyakit darah tinggi. Pada remaja, hipertensi juga merupakan suatu masalah, oleh karena remaja yang mengalami hipertensi dapat terus berlanjut pada usia dewasa dan memiliki resiko morbiditas dan mortalitas yang lebih tinggi. Menurut data Riskesdas tahun 2007, prevalensi hipertensi pada remaja sebesar 9%.  Prevalensi obesitas pada remaja menurut data Riskesdas 2010 sebesar 19,1%. Penelitian ini bertujuan untuk mengetahui gambaran tekanan darah pada remaja obes di kabupaten Minahasa. Penelitian ini bersifat cross-sectional dengan pendekatan deskriptif. Sampel penelitian ini berjumlah 54 orang. Hasil pemeriksaan didapati  104 siswa yang memiliki lingkar pinggang lebih dari normal. Hasil penelitian menunjukkan  gambaran tekanan darah pada remaja obes di kabupaten Minahasa didapatkan 29,62% yang menderita hipertensi.      Terdapat 16 subjek dari 54 subjek yang diteliti memiliki tekanan darah lebih dari batas normal sedangkan 38 subjek memiliki tekanan darah dalam batas normal. Kata kunci: Obesitas, Tekanan Darah